Possibilities of the ecological model application for reconstruction of economy in prehistoric populations - Ostoja-Zagórski, Janusz (Anthropological Review, 1978)
The ecological model applied here was constructed in collaboration with M. Henneberg. It is based on the fundamental biological theorem pertaining to adaptive relations between population and environment. The model is constructed with the use of the idealization method whereby it is recognized that each phenomenon has a main, primary aspect and secondary ones that may be overlooked. The primary aspects, when one is considering our prehistory, of the economic structure of a given population are, first of all: natural environment, settlement pattern, population demographic structure, its basic needs, and working time that was required to satisfy these needs. When applying the proposed method, we have found that the amount of working time at the population's disposal was far greater than the amount of work required to satisfy basic needs. We are able to conclude that a population was economically self-sufficient in given environmental conditions. Disturbances concerning shifts in settlement pattern, economy, etc. are in such a situation due to external factors (mainly changes in the natural environment) that were uncontrollable by the people.